Opposite outcomes of triglyceride-glucose index and associated cardiovascular mortality risk in type 2 diabetes mellitus participants by different obesity criteria - Hui Huang; Jing Tian; Jiahui Xu; Qingguang Chen; Mengjie Cai; Hao Lu; Fan Gong (Scientific Reports)
Abstract We investigated the correlation between Triglyceride-glucose (TyG) index and cardiovascular disease (CVD) mortality in type 2 diabetes mellitus (T2DM) population across different obesity classications using a cohort study. We analyzed 7867 T2DM participants from the National Health and Nutrition Examination Survey 1999–2018, categorizing them into obese or non-obese group by body mass index (BMI) and waist circumference (WC). Cox regression models were used to estimate the correlation between TyG index and CVD mortality risk, comparing the results across the two obesity classifications. Over a 9.1-year follow-up, 691 CVD deaths occurred. Among non-obese T2DM participants (BMI-defined), the hazard ration for CVD mortality was 1.73 in the fourth quartile group of TyG index compared with the first quartile group. Conversely, among obese T2DM participants (WC-defined), the fourth quartile group of TyG index held a 1.51-fold risk of CVD mortality compared with the first quartile group. The association between obesity and higher CVD risk was observed in WC-defined obesity but not in BMI-defined obesity. A totally opposite relationship appeared between TyG index and CVD mortality based on how obesity was defined using BMI or WC in the T2DM participants, suggesting a reevaluation of BMI’s accuracy in predicting mortality risk.